Counselling in infertility: Individual, couple and group interventions - Broeck, Uschi van den; Emery, Marysa; Wischmann, Tewes; Thorn, Petra (Patient education and counseling, 2010)
Infertility is considered a biopsychosocial crisis and infertility counselling is recommended as an integral part of a multidisciplinary approach. This article will outline the theoretical background and describe common interventions used in infertility counselling for individuals, couples and in a group setting.